KARAKTERISTIK FISIK RUMAH DENGAN KEJADIAN TB PARU DI WILAYAH KERJA PUSKESMAS SEI JANG KOTA TANJUNGPINANG - Indra Martias; Hendra Dhermawan Sitanggang (Jurnal Riset Kesehatan, 2018)
Tuberculosis remains a public health problem in Indonesia. While the percentage of unhealthy homes in Indonesia is still high at 75.1% and in the Riau Islands 76,3%. Construction of houses and the neighborhood does not meet health requirements would be a risk factor for pulmonary tuberculosis transmission source. This study aims to determine the relationship between the physical characteristics of the home (residential density, types of flooring, ventilation, lighting, temperature and humidity) and the incidence of pulmonary tuberculosis in Puskesmas Sei Jang Tanjungpinang. This study uses a case control design were analyzed by chi-square test and Fisher exact. The number of samples in this study were 36 cases and 36 controls. Cases were all TB patients with sputum examination results at the health center laboratory stated smear positive (suffering from pulmonary TB) 2016 to June 2017. Control is a neighboring group of cases have a history of not suffering from pulmonary TB. Results showed that the floor of the house (OR = 2.12; 95% CI: 0.364 to 12.049), ventilation (OR = 3.4; 95% CI 0.638 to 18.132), lighting (OR = 2.08; 95% CI: 0.779 to 5.552), population density (OR = 2.5; 95% CI: 0.962 to 6.498), and humidity (OR = 2.742; 95% CI: 0.496 to 15.168) who do not qualify is a risk factor to the incidence of pulmonary tuberculosis. However, this study found no statistically significant relationship. Suggested to the respondents whose homes are not eligible to be regularly open the window every morning before going on air circulation and sunlight can kill the TB germs.